Comparative analysis of PD‐1 target engagement of dostarlimab and pembrolizumab in advanced solid tumors using ex vivo IL‐2 stimulation data. (16th November 2022) - Austin, Daren; Melhem, Murad; Gandhi, Yash; Lu, Sharon; Visser, Sandra
Abstract: Dostarlimab (JEMPERLI) is an anti‐programmed cell death protein‐1 (PD‐1) monoclonal antibody (mAb) which is approved by the US Food and Drug Administration for patients with recurrent/advanced mismatch repair‐deficient solid tumors, including endometrial cancer, following progression on prior treatment, with approval based on data from the phase I GARNET trial. To support dostarlimab dose regimen recommendations, we estimated and compared the potency of dostarlimab relative to anti–PD‐1 mAb pembrolizumab using both data published from the KEYNOTE‐001 trial of pembrolizumab and data from the GARNET trial. PD‐1 target engagement was assessed ex vivo in blood samples via a super antigen staphylococcal enterotoxin B stimulation assay and interleukin‐2 (IL‐2) stimulation ratios calculated for dostarlimab. A non‐linear mixed‐effect sigmoid maximum effect inhibitory model was fitted to dostarlimab IL‐2 stimulation ratios using extracted pembrolizumab data as informative priors. The estimated half‐maximal effective concentration was 1.95 μg ml −1 (95% credibility interval: 0.21–5.87) for dostarlimab and 1.59 μg ml −1 (95% confidence interval: 0.42–6.12) for pembrolizumab. These findings suggest dostarlimab and pembrolizumab to be equipotent for peripheral PD‐1 suppression based on analysis of ex vivo IL‐2 stimulation ratios. Accounting for a three‐fold dilution between serum and tumor, a target dostarlimab trough concentration of 54 μg ml −1 would be needed for 90% suppression in the tumor. These data support the use of dostarlimab as a potent PD‐1 suppressor and the recommended dostarlimab monotherapy dose regimen of 500 mg Q3W ×4 cycles followed by 1000 mg Q6W thereafter in recurrent/advanced solid tumors.